Exploring the potential of tetraazaacene derivatives as photovoltaic materials with enhanced photovoltaic parameters. Issue 1 (4th September 2021) - Fatima, Rida; Shehzad, Rao Aqil; Rasool, Alvina; Yaseen, Muhammad; Iqbal, Saleem; Saif, Muhammad Jawwad; Iqbal, Javed
Abstract: A series of D‐π‐A type molecules have been designed for their potential use in organic photovoltaic devices. Photovoltaic and optoelectronic properties of newly designed molecules have been explored by comparing with a reference molecule R comprising of the central core (2, 3, 8, 9‐tetrakis(thiophen‐2‐ylethynyl)‐5, 7, 10, 12‐tetrakis((trimethylsilyl)ethynyl)pyrazino[2, 3‐b]phenazine) and π‐bridge (thiophene). The end groups are (2‐(2‐ethylidene‐3‐oxo‐2, 3‐dihydro‐1H‐inden‐1 ylidene)malononitrile), (2‐ethylidenemalonitrile), (methyl 2‐cyanoacrylate) and (3‐methyl‐5‐methylene‐2‐thioxothiazolidin‐4‐one) in the newly designed molecules. Among the investigated molecules M1 and M2 exhibit a broad absorption range of 627 and 626 nm with respect to the reference. All the designed molecules exhibited a lower bandgap as compared to R which indicates a better transfer of electron density from highest occupied molecular orbital (HOMO) to lowest unoccupied molecular orbital (LUMO). The reorganization energy values show that all designed molecules have efficient charge transport capability. This study proves that end‐capped acceptor modification is an effective strategy for designing optimistic molecule for high performance future organic solar cells fabrication. Abstract : Tetraazaacene based small organic molecules are designed with enhanced optoelectronic properties using a quantum chemical approach. These molecules have shown lower bandgap that is suitable for proficient solar cells. The introduction of acceptor groups is mainly responsible for the enhancement of photophysical properties of the designed molecules.